Iceland : Request for Stand-By Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2008)
This paper examines key findings of Iceland's Request for a Stand-By Arrangement from the IMF. Iceland's economy is in the midst of a banking crisis of extraordinary proportions that is expected to lead to a deep recession, a sharp rise in the fiscal deficit, and a dramatic surge in public sector debt, reflecting a high fiscal cost of restructuring the banking system. The virtual collapse of the on-shore foreign exchange market poses a serious and immediate risk to the economy considering its high import dependence.